2020
DOI: 10.1101/2020.10.05.20206953
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Scalable, effective, and rapid decontamination of SARS-CoV-2 contaminated N95 respirators using germicidal ultra-violet C (UVC) irradiation device

Abstract: Importance: Particulate respirators such as N95 masks are an essential component of personal protective equipment (PPE) for front-line workers. This study describes a rapid and effective UVC irradiation system that would facilitate the safe re-use of N95 respirators and provides supporting information for deploying UVC for decontamination of SARS-CoV-2 during the COVID19 pandemic. Objective: To assess the inactivation potential of the proposed UVC germicidal device as a function of time by using 3M 8211 - N95 … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(26 citation statements)
references
References 25 publications
1
24
0
Order By: Relevance
“…Considering the studies in the SLR’s final database, 31 studies [ 1 , 6 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 49 , 50 , 52 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 63 , 64 , 65 , 66 , 85 ], representing 53.45% of the SLR database, attest to UV-C’s germicidal capability, as they find results of at least 3-log reduction using different biological indicators, conditions, and setups. These studies present results using UV-C as a single method of sterilization.…”
Section: Uv-c’s Germicidal Capabilitymentioning
confidence: 99%
See 3 more Smart Citations
“…Considering the studies in the SLR’s final database, 31 studies [ 1 , 6 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 49 , 50 , 52 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 63 , 64 , 65 , 66 , 85 ], representing 53.45% of the SLR database, attest to UV-C’s germicidal capability, as they find results of at least 3-log reduction using different biological indicators, conditions, and setups. These studies present results using UV-C as a single method of sterilization.…”
Section: Uv-c’s Germicidal Capabilitymentioning
confidence: 99%
“…Ultraviolet-C is normally regarded as a low-cost reprocessing method. From the SLR’s final sample, most publications used either adapted biosafety [ 6 , 49 , 50 , 57 , 58 , 59 , 61 , 83 ] or sterilization [ 33 , 56 , 86 ] cabinets; adapted chambers [ 7 , 39 , 43 , 48 , 64 , 66 , 75 , 78 ], rooms [ 51 , 68 , 69 , 85 ] or laminar flow cabinets [ 43 , 71 , 80 , 82 ]; the lamps alone [ 38 , 40 , 46 , 52 , 54 , 63 , 79 , 87 ] or tube racks [ 70 ]. Most of these resources are available in research departments or hospitals; making this method “reasonably (…) inexpensive” [ 7 ] (p. 515) or, at least, “a cost-effective alternative to heat or chemical decontamination” [ 69 ] (pp.…”
Section: Uv-c’s Additional Advantagesmentioning
confidence: 99%
See 2 more Smart Citations
“…The four major structural proteins include the spike surface glycoprotein (S) ( 31 ), envelope protein (E) ( 32 ), membrane (M) ( 33 ) and nucleocapsid protein (N) ( 34 ). Recent studies have revealed six major NSP subtypes, including nsp3 ( 35 ), nsp4 ( 36 ), nsp6 ( 37 ), nsp12 ( 38 ), nsp13 ( 39 ) and nsp14 ( 38 ) for SARS-CoV-2. Spike proteins of viruses bind to host cell receptors for entry.…”
Section: Structure Genome Size and Life Cycle Of Sars-cov-2mentioning
confidence: 99%